Situation Report: Romania, 27 October 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Celebration of the Army Day Romanian-Pakistani Communique Economic Directives on Agriculture Relations with the FRG Miscellaneous